Genetics and Breeding for Glandless Upland Cotton With Improved Yield Potential and Disease Resistance: A Review - Zhang, Jinfa; Wedegaertner, Tom (Frontiers in Plant Science, 2021)
Glandless cotton (devoid of toxic gossypol) can be grown as a triple-purpose crop for fiber, feed and food (as oil and protein source). However, its sensitivity to insect pests and low yield due to the lack of breeding activities for glandless cotton has prevented the realization of its potential in commercial seed production and utilization. Since the mid-1990s, the commercialization of bollworm and budworm resistant Bt cotton and eradication of boll weevils and pink bollworms has provided an opportunity to revitalize glandless cotton production in the U.S. The objectives of this study were to review the current status of genetics and breeding for glandless cotton, with a focus on the progress in breeding for glandless Upland cotton in New Mexico, USA. Because there existed a 20-50% yield gap between the best existing glandless germplasm and commercial Upland cultivars, breeding for glandless Upland cultivar with improved yield and disease resistance was initiated at New Mexico State University more than a decade ago. As a result, three glandless Upland cultivars, i.e., long staple Acala 1517-18 GLS, and medium staple NuMex COT 15 GLS and NuMex COT 17 GLS with Fusarium wilt race 4 resistance were released. However, to compete with current commercial glanded cotton, more breeding efforts are urgently needed to introduce different glandless traits (natural mutations, transgenic or genome-editing) into elite cotton backgrounds with high yields and desirable fiber quality.